Chlamydia Peritonitis Mimicking Juvenile Carcinomatous Peritonitis Diagnosed by Exploratory Laparoscopy: A Case Report - Haruka Nishida; Yuko Takahashi; Kohei Takehara; Keita Yatsuki; Takayuki Ichinose; Tsuyoshi Ishida; Haruko Hiraike; Yuko Sasajima; Kazunori Nagasaka (Pathogens, 2023)
Chlamydia trachomatis infections may occur in multiple organs, including the lungs, lymph nodes, peritoneal cavity, and genitourinary systems. This disease results in significant ascites, the swelling of lymph nodes, and elevated tumor markers (CA125), sometimes mimicking an ovarian malignancy. At our hospital, we often perform examination laparoscopic surgery in cases of suspected gynecologic cancers before initial treatment. In this paper, we report the case of a 19-year-old woman who came to our hospital because of an ovarian tumor and ascites. There was no history of sexual intercourse (self-reported). We suspected ovarian cancer from image inspections, so we performed laparoscopic surgery for diagnosis. The final pathological diagnosis was acute-to-chronic inflammation of the bilateral fallopian tubes, and a cytologic examination of the ascites was negative for malignant cells. The C. trachomatis antigen was positive on vaginal examination after the operation. Based on this result, we diagnosed this patient with C. trachomatis infection. Chlamydia peritonitis should be a differential diagnosis for cancer peritonitis in juvenile patients with abnormal ascites. Exploratory laparoscopy should help confirm the pathological diagnosis.